Push, pull, squeeze, clamp: 100 years of changes in the management of the third stage of labour as described by Ten Teachers. (19th December 2012) - Aflaifel, Nasreen; Weeks, Andrew
Abstract : Should we look back at historical methods to see if we are missing a trick? Aflaifel and Weeks trace the history of managing the third stage of labour